Comparison Of The Antibacterial Activity Of Palm Kernel Oil (PKO) & Virgin Coconut Oil (VCO) Against Pseudomonas Aeruginosa Bacteria - Juwita Purnamasari; Sri Wahyuni Gayatri B; Andi Sitti Fahirah Arsal; Aryanti R. Bamahry; Marzelina Karim (CV. Inara, 2025)
Pseudomonas aeruginosa, a gram-negative bacterium, is a significant cause of nosocomial infections and exhibits high levels of multidrug resistance, necessitating the exploration of alternative antibacterial agents. This study investigates the antibacterial activity of Palm Kernel Oil (PKO) and Virgin Coconut Oil (VCO) against Pseudomonas aeruginosa, employing a true experimental post-test design with microdilution and agar dilution methods. Conducted at the Universitas Muslim Indonesia, the study determined the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of PKO, VCO, and gentamicin. Results revealed that PKO had an MIC of 4096 µg/mL and an MBC of 8192 µg/mL, while VCO exhibited an MIC of 2048 µg/mL and an MBC of 4096 µg/mL. Gentamicin, used as a control, demonstrated superior antibacterial effectiveness with an MIC of 2 µg/mL and an MBC of 4 µg/mL. Statistical analysis indicated that VCO, with its higher lauric and myristic acid content, was more effective than PKO in inhibiting bacterial growth, although both oils were less effective than gentamicin. The study highlights the potential of VCO as a natural antibacterial agent, suggesting further research to optimize its efficacy through formulation modifications and combinations with other antimicrobial agents. Additionally, evaluating the effectiveness of VCO and gentamicin against other bacterial strains is recommended to expand the understanding of VCO's antibacterial capabilities. These findings contribute to the growing body of evidence supporting the use of natural products in combating antibiotic-resistant infections.